مهارات الإتصال غير اللفظية في السنة النبوية - الجنوبي، عواطف بنت علي محمد Aljanoubi, Awatef Bint Ali Mohammed (جامعة الأميرة نورة بنت عبد الرحمن, 2018)
إن المرء في تفاعله مع من حوله يستخدم لغة لفظية وغير لفظية بصورة مستمرة ودائمة، ولكل من هاتين اللغتين في التفاعل الإنساني جوانب وميزات تؤثر على علاقته بالآخرين سلباً أو إيجاباً حسب مقدرته على استثمار آلياتها. وحينما يقف المرء ليفصح عن أمر ما، فإن جسده أيضاً يتحدث ويخاطب الآخرين سواءً بصورة إرادية أو غير إرادية، وهذا ما يسمى باللغة غير اللفظية، وهي لغة لا يحكيها اللسان، بل يتولاها الجسد من أعلى الراس حتى أخمص القدم. وكما أن اللغة اللفظية ذات ميزات ومؤثرات، فإن اللغة غير اللفظية لا تقل عنها أثراً وقوة في توجيه الأفراد أو الجماعات، لذا جاء الاهتمام بهذا البحث لإبراز جوانب المهارة غير اللفظية في التواصل النبوي الذي تجلى من خلاله أقوى مهارة ومقدرة للمصطفى صلى الله عليه وسلم في توظيف هذه اللغة، توظيفاً تميز بفعاليته. هذه الفعالية التي تجلت في استخدامها بالموضع المناسب دون قصور أو إسراف، حسب حاجة الموقف. ولم يكن من الهين الخوض في هذا الموضوع، نظراً لصعوبة تنزيل الأحاديث على قواعد الاتصال المدونة في كتب مهارات الاتصال، مما دفع إلى وضع تفريعات تتلاءم مع واقع السنة النبوية، فتم تفريع لغة الجسد إلى : تواصل عن بعد (بدون لمس)، وتواصل باللمس، وهذا مما لم أقف عليه فيما راجعت من كتب الاتصال، ولكونه يستوعب ما ورد في سيرة المصطفى صلى الله عليه وسلم، وأنفع في تنظيم البحث، وأيسر للقارئ العادي جرى اتخاذه. Any person interacting with others uses a continuous combination of verbal and non - verbal languages, and each of these two human interaction languages has its own aspects and features that affects a person’s relationships with others, depending on how well s/he employs the mechanisms of each. When one stands to express himself, his or her body also talks and engages with others, whether in a voluntary on involuntary manner. This is termed non-verbal language, a language not spoken by the tongue, but instead performed by one's body. As verbal language has its own features and effects, non - verbal language is no less powerful and effective in directing individuals and groups, and it is for this reason that this research was chosen to highlight the aspects of the non - verbal language present in the Prophet Muhammad's - pbuh - communication, through which the skill and ability of the Prophet Muhammad - pbuh - in using such language is evident. This effectiveness can be seen in using the best suited non-verbal language in the right place, without any lack thereof or excessiveness, depending on the need of the situation. It was not easy to delve into this topic, due to the difficulty of categorising ahadeeth based on the principles of communication found in the books on communication skills, which led to the imposition of sub - parts more compatible with the sunnah of the Prophet - pbuh -, so body language was divided into: distant communication (without touch) and communication with touch. And this is what I did not come across in the various books on communication, but it encompasses the seerah of the Prophet – pbuh - and is more effective in organising the research, and is also easier for the lay reader.
Keywords: السنة النبوية -- لغة الجسد -- التواصل النبوي -- علم الإتصال غير اللفظي -- الدراسات الإسلامية